Food, Gender, and Social Status in Rural Parts of North-West India: A Case Study of Rajasthan - Vikas Mohan; Reema Gill (Gastronomy Tourism Journal, 2023)
The purpose of this research is to investigate the relationship between eating habits, gender roles, and social status in rural areas of North-West India, with a particular emphasis on the part that women play in the production and consumption of food. This study investigates the ways in which cultural and social standards influence food practices and preferences among women and men of different social and economic backgrounds by conducting ethnographic research and in-depth interviews with rural households in different regions of Rajasthan. According to the findings of this research, women's eating behaviours are frequently restricted by gender roles and expectations, which in turn restricts their access to food resources and their ability to make decisions regarding the food that they consume. In addition, it was discovered that social standing and caste play a significant role in shaping food practises and preferences, with households of higher castes typically consuming more expensive and nutritionally dense food items. In its conclusion, the study highlights the necessity of interventions that are culturally appropriate and gender-sensitive. These interventions should address the underlying social and cultural factors that contribute to gender and social disparities in food access and consumption in rural areas of Rajasthan.